On valuing truth in practice: Rome's postmodern challenge - Murray, Paul D. (2007)
This essay probes whether there can be any real and fruitful dialogue between Roman Catholic self-understanding in relation to truth and postmodern questioning of the value of all such truth-talk, at least as traditionally conceived. After an introductory section situating the essay in context, the exploration moves through four phases. First, there are some initial reflections on the place of truth in Catholic self-understanding and the significant shaping force this exerts on Catholic structure and practice. Second, attention shifts to asking after the motivating factors behind Rorty’s trenchant disavowal of ‘objectivity’ in favour of ‘solidarity’, or localised agreement, as the only viable basis for interpreting and acting within the world. Having noted the challenges that Rorty’s concerns pose to Catholic self-understanding, attention turns in the third part to review the counter-case that can be made for the lasting significance of a revised aspiration for truth as the articulation of reality. The final section further probes the challenge that this position in turn holds for the concern that Catholicism give appealing, inspiring, convincing and, in this sense, authoritative witness to the task of discerning together the truth in love.